Evaluation of yield and groundwater quality for selected wells in Malaysia - Mohammed, Thamer Ahmed; Ghazali, Abdul Halim (Universiti Putra Malaysia Press, 2009)
In Malaysia, the use of groundwater can help to meet the increasing water demand. The utilization of the aquifers is currently contributing in water supplies, particularly for the northern states. In this study, quantitative and qualitative assessments were carried out for the groundwater exploitation in the states of Kelantan, Melaka, Terengganu and Perak. The relevant data was acquired from the Department of Mineral and Geoscience, Malaysia. The quantitative assessment mainly included the determination of the use to yield ratio (UTY). The formula was proposed to determine the UTY ratio for aquifers in Malaysia. The proposed formula was applied to determine the maximum UTY ratios for the aquifers located in the states of Kelantan, Melaka, and Terengganu, and were found to be 4.2, 5.2 and 0.6, respectively. This indicated that exploitation of groundwater was beyond the safe limit in the states of Kelantan and Melaka. The qualitative assessment showed that the groundwater is slightly acidic. In addition, the concentrations of iron and manganese were found to be higher than the allowable limits, but the chloride concentration was found within the allowable limit.